2020
DOI: 10.3390/ijms21041338
|View full text |Cite
|
Sign up to set email alerts
|

Phytotoxicity, Bioaccumulation, and Degradation of Nonylphenol in Different Microalgal Species without Bacterial Influences

Abstract: Nonylphenol (NP) is a contaminant that has negative impacts on aquatic organisms. To investigate its phytotoxicity, bioaccumulation, and degradation in algae without associated bacteria, six freshwater microalgae—Ankistrodesmus acicularis, Chlorella vulgaris, Chroococcus minutus, Scenedesmus obliquus, Scenedesmus quadricauda, and Selenastrum bibraianum—in bacteria-free cultures were studied. When exposed to 0.5–3.0 mg L−1 NP for 4 days, cell growth and photosynthesis, including maximal photochemistry (Fv/Fm), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Inhibition of TH-binding by OP might damage the TRH–TSH–THs regulatory pathway. In addition, APs might accelerate the TH metabolic rate by enhancing the activity of iodothyronine deiodinase, leading to a decrease in T 3 and T 4 activity (He et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of TH-binding by OP might damage the TRH–TSH–THs regulatory pathway. In addition, APs might accelerate the TH metabolic rate by enhancing the activity of iodothyronine deiodinase, leading to a decrease in T 3 and T 4 activity (He et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, when combined with conventional activated sludge systems, algal-bacterial symbiosis can reduce the electrical energy requirements for aeration (Redalje et al 1989). Other advantages can be found in the following references: Biris-Dorhoi et al 2016, Hwang et al 2016, Molazadeh et al 2019, and Wollmann et al 2019 Recent studies have also been reported the removal, biosorption and biodegradation of alkylphenols by microalgae (Zhou et al 2013(Zhou et al , 2014Delrue et al 2016;He et al 2016He et al , 2020Maza-Márquez et al 2018;Gupta and Bux 2019;Wang et al 2019). For example, Zhou et al (2013Zhou et al ( , 2014 studied the removal of nonylphenol and octylphenol by the freshwater green microalga Scenedesmus obliquus in cultures exposed to different concentrations of alkylphenols for 5 days.…”
Section: Microalgae-based Technologymentioning
confidence: 99%
“…Recent studies have also been reported the removal, biosorption and biodegradation of alkylphenols by microalgae (Zhou et al 2013(Zhou et al , 2014Delrue et al 2016;He et al 2016He et al , 2020Maza-Márquez et al 2018;Gupta and Bux 2019;Wang et al 2019). For example, Zhou et al (2013Zhou et al ( , 2014 studied the removal of nonylphenol and octylphenol by the freshwater green microalga Scenedesmus obliquus in cultures exposed to different concentrations of alkylphenols for 5 days.…”
Section: Alkylphenol Removal Using Microalgaementioning
confidence: 99%